Design of Sensor-Based Left Muscle Power Testing Tool - Asep Suharta; Nurkadri Nurkadri; Rahma Dewi; Amir Supriadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to develop a power tool where the test tool changes the manual to digital concept and a manual for the use of the test tool was developed. The products produced are the Power, and the manual for the use of the Power. This research was developed by adapting the research and development of the Borg & Gall model. The development procedure used includes several stages: 1) analyzing the content of the product being developed, 2) developing the initial product, 3) expert validation, 4) field testing, 5) product revision. qualitative. sampling technique used purposive sampling with a Phase I trial of 20 FIK students and a Phase II trial of 30 athletes from PON SUMUT. Furthermore, from the Phase I trial, which amounted to 20 people, the figure was 96% with Very Eligible, then from the Phase II trial, which amounted to 30 PON SUMUT athletes, it showed a figure of 91% in the Eligible